2009
DOI: 10.1051/0004-6361/200810742
|View full text |Cite
|
Sign up to set email alerts
|

On the metal abundances inside mixed-morphology supernova remnants: the case of IC 443  and G166.0+4.3

Abstract: Context. Recent developments in the study of mixed morphology supernova remnants (MMSNRs) have revealed the presence of metal-rich X-ray emitting plasma inside a fraction of these remnants, a feature not properly addressed by traditional models for these objects. Aims. Radial profiles of thermodynamical and chemical parameters are needed for a fruitful comparison of data and model of MMSNRs, but these are available only in a few cases. Methods. We analyzed XMM-Newton data of two MMSNRs, namely IC 443 and G166.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 34 publications
1
27
1
1
Order By: Relevance
“…4.10 G166.0+4.3, VRO 42.05.01 G166.0+4.3 has an unusual shape consisting of two radio shells with significantly different radius. Bocchino et al (2009) classify G166.0+4.3 as an MM (Mixed-morphology) SNR. This unusual morphology and different radius may be explained by the different gas environments on both sides.…”
Section: G2069+23 Pks 0646+06mentioning
confidence: 99%
“…4.10 G166.0+4.3, VRO 42.05.01 G166.0+4.3 has an unusual shape consisting of two radio shells with significantly different radius. Bocchino et al (2009) classify G166.0+4.3 as an MM (Mixed-morphology) SNR. This unusual morphology and different radius may be explained by the different gas environments on both sides.…”
Section: G2069+23 Pks 0646+06mentioning
confidence: 99%
“…It is also among the brightest gamma-ray SNRs in the MW (e.g., Esposito et al 1996;Sturner & Dermer 1995;Acciari et al 2009;Ackermann et al 2013). In addition to a number of radio studies (Braun & Strom 1986;Snell et al 2005), this remnant has been extensively followed up in X-rays (e.g., Petre et al 1988;Kawasaki et al 2002;Troja et al 2006Troja et al , 2008Bocchino et al 2009;Yamaguchi et al 2009;Ohnishi et al 2014). Originally, Troja et al (2008) suggested that the X-ray emission of IC 443 could be well described by a two-component plasma, one low temperature (kT ≈ 0.30 − 0.50 keV), NEI component associated with shocked ISM and a hot, (kT ≈ 1.10−2.00 keV) ejecta component in CIE with supersolar abundances of Mg, Si and S. However, analysis of ASCA and Suzaku observations revealed that an additional low temperature (kT ≈ 0.60 keV), overionized plasma component is necessary to account for the line ratios and the radiative recombination continua features in the spectra (Kawasaki et al 2002;Yamaguchi et al 2009;Ohnishi et al 2014).…”
Section: Properties Of the Snrsmentioning
confidence: 99%
“…At present, there are ∼ 40 known MM SNRs (see summary by Vink 2012), but the nature of the central X-ray emission is poorly understood. While abundance determinations from X-ray spectra indicate evidence for the presence of ejecta in some such remnants (e.g., Shelton et al 2004;Lazendic and Slane 2006;Bocchino et al 2009;Pannuti et al 2010;, the estimated mass of X-ray emitting material in the central regions is generally much too high to be composed primarily of ejecta.…”
Section: Mixed Morphologymentioning
confidence: 99%
“…The roughly solar abundances for this swept-up material will thus act to severely dilute the enhanced abundances of any (much smaller) ejecta component. Nonetheless, traces of ejecta appear common in many mixed morphology remnants (e.g., Slane et al 2002;Shelton et al 2004;Lazendic and Slane 2006;Bocchino et al 2009), virtually all of which appear to be interacting with molecular clouds. In IC 443, a distinct ring-like structure of hot (∼ 1.4 keV) plasma with significantly enhanced abundances of Mg and Si is observed in the vicinity of a MC interaction region, suggesting that a strong reverse shock produced in this interaction with dense material has produced enhanced ejecta emission (Troja et al 2008).…”
Section: Abundances and Nonthermal Emissionmentioning
confidence: 99%